Dispersion of graphene nanoplatelets in poly(vinyl acetate) latex and effect on adhesive bond strength - Artur M. Pinto (2013)
Graphene nanoplatelets (GNPs) were directly dispersed in poly(vinyl acetate) (PVAc) latex in concentrations from 0.05 up to 2 wt% (based on dry weight), without using additional surfactants or dispersants. Stable dispersions were obtained due to interaction of the GNPs with protective colloids (poly(vinyl alcohol) and hydroxyethylcellulose) originally present in the latex. This caused an increase in viscosity and accentuated the pseudoplastic behavior of the latex, as evidenced by rheological measurements. Cryo-SEM imaging showed that individual nanoplatelets were present in the aqueous phase. The equilibrium contact angle for water on dry PVAc films increased by 13 degrees upon incorporation of 0.1 wt% GNPs due to the nanofiller hydrophobicity. However, this increase was lower for higher loadings, probably due to the occurrence of GNP agglomeration. Bond strength measurements performed with an automated bonding evaluation system setup on veneer lap joints showed more than 50% shear strength increase with incorporation of only 0.10.3 wt% GNPs. At higher loadings the bond strength decreased, indicating less efficient nanofiller dispersion in the polymer matrix. Raman spectroscopy analysis confirmed that GNP agglomeration was more significant at higher loadings.